Exploring Factors Contributing to Math Teachers’ Experiences in Certification Examinations - Amrahova, Ravana; Guliyeva, Gultakin; Farzandli, Arzu; Babayeva, Nargiz; Aghayeva, Sevinj (ADA University, 2025)
Enhancing teaching effectiveness is vital to national educational policies in most countries, including Azerbaijan. For this reason, teachers’ professional development through the certification process is fundamental in Azerbaijan. Thus, understanding teachers' experiences in the certification examinations is key to developing policies that can further support teachers’ professional growth and, in turn, the overall quality of education. Since math teachers recently took the exam in Azerbaijan, we decided to explore the factors that contribute to their experiences in certification examinations and their preparation strategies for the exam. In this study, semi-structured interviews were conducted with 17 math teachers in both online and in-person formats: seven teachers from rural areas (three failed, four passed) and ten teachers from urban areas (four failed, six passed). The results indicate that individual and structured preparation, time constraints, family obligations, exam format and question complexity, regular practice and tutoring experience, digital literacy and technical issues, as well as psychological factors, are primary contributors to math teachers' experiences in certification examinations in Azerbaijan. Regarding preparation strategies, consistent and disciplined preparation, use of digital platforms, test-centered practice, collective preparation, and peer collaboration are found to be the most utilized approaches to prepare for the exam; however, several teachers also reported a lack of preparation or strategy during the interviews. Moreover, the teachers were asked to suggest strategies that could be useful for future certification candidates, which include self-study and continuous practice, emphasis on test-based preparation, development of subject knowledge, and psychological readiness. At the end, as a final product, we suggest a guideline kit to math teachers that addresses effective planning using the SMART goals method and individualized study planners, clearly understanding the exam format to avoid any confusion, managing psychological stress and building self-confidence through stress management techniques, acquiring essential digital skills needed for the computer-based test, and fostering a supportive learning environment among peers to collaboratively prepare for the certification exam.
Keywords: Teacher certification -- Azerbaijan; Professional development of teachers -- Azerbaijan; Mathematics teachers -- Certification -- Azerbaijan; Digital literacy -- Education; Teacher attitudes; Education